Design of a wideband miniature dielectric-filled waveguide antenna for collision-avoidance radar. - Hajian, M.; Tran, D.P.; Ligthhart, L.P.
This article presents a theoretical and experimental study of the design of a miniaturized wideband dielectric-filled waveguide (DFW) antenna. The operational frequency is X band, i.e., 9.0⩽f⩽10.5 GHz. The desired bandwidth is 1.5 GHz. The antenna uses an air-gap matching network to reduce its high aperture reflection. In order to ease the integration with antenna circuits and to increase the bandwidth, two E-plane steps are used. The antenna is designed to have -3 dB beamwidths of 60° and 100° for the E- and H-plane patterns, respectively. An input reflection of less than -10 dB for the desired bandwidth is observed. The gain of the antenna is 7 dBi. A cross-polar level of less than -25 dB is achieved. This article discusses the mathematical model for input reflection, the design scenarios, and the experimental results.
Keywords: Dielectric antennas; Waveguide antennas; Road vehicle radar; Wideband antennas; FM radar; CW radar